Un país de remadores: canoas, monterías y batelones en el boom del caucho (Amazonía boliviana, 1870-1920) - Villar, Diego (Anuario de Historia de América Latina, 2020)
The paper analyzes historical sources (rubber tappers, travelers, explorer, scientific, military, and missionary accounts) in order to describe rowing navigation during the rubber boom in Bolivian Amazonia (1870-1920). Technical features of several types of boats are described, as well as the navigation skills involved, the unstable labor conditions, the natural and geographical obstacles, the sociological and ethnic substratum of the fluvial workforce and some of the dilemmas and ambiguities of rubber extractivism. Then the paper analyses the combination of specific navigation factors, the scarcity of labor and the regional and global demand of rubber that helped the fluvial crews to gain gradually strategic autonomy and a set of civil and laboring rights.
Keywords: Bolivia, Amazonia, Navigation, Rivers, Indigenous peoples, Extractive industries, Rubber boom